2017
DOI: 10.1093/mnras/stx2475
|View full text |Cite
|
Sign up to set email alerts
|

H i debris in the IC 1459 galaxy group

Abstract: We present H i synthesis imaging of the giant elliptical galaxy IC 1459 and its surroundings with the Australia Telescope Compact Array (ATCA). Our search for extended H i emission revealed a large complex of H i clouds near IC 1459, likely the debris from tidal interactions with neighbouring galaxies. The total H i mass (∼ 10 9 M ) in the detected clouds spans 250 kpc from the north-east of the gas-rich spiral NGC 7418A to the south-east of IC 1459. The extent and mass of the H i debris, which shows rather ir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 58 publications
(79 reference statements)
7
40
0
Order By: Relevance
“…This is particularly interesting as substantial H I debris are often found near massive, early-type galaxies (see e.g. Chung et al 2009;Saponara et al 2018). The pair is also part of the subgroup containing NGC 5150.…”
Section: E N V I Ro N M E N T a N D H I M O R P H O L O G Ymentioning
confidence: 95%
“…This is particularly interesting as substantial H I debris are often found near massive, early-type galaxies (see e.g. Chung et al 2009;Saponara et al 2018). The pair is also part of the subgroup containing NGC 5150.…”
Section: E N V I Ro N M E N T a N D H I M O R P H O L O G Ymentioning
confidence: 95%
“…The long tidal tails, high gas content and shells are indicative of two merging spirals (e.g., Toomre & Toomre 1972;Toomre 1977;Malin & Carter 1980). Saponara et al (2018) found large HI clouds near IC 1459, concluding these were likely to be debris from tidal interactions with neighbouring galaxies. Being the central galaxy in a relatively small group would mean a high probability of mergers due to the low dispersion of the group (Ostriker 1980;Tremaine 1981).…”
Section: Merging Spiralsmentioning
confidence: 99%
“…While all forms of hydrogen are typically detected in the inner discs and spiral arms of galaxies in the Local Universe, most often it is the H I 21-cm line that reveals the outermost regions of galaxy discs (e.g., Warren et al 2004;Begum et al 2005;Sancisi et al 2008;Heald et al 2011;Koribalski et al 2018). Occasionally H I is found in filaments, plumes and/or bridges, tracing the gravitational interactions with neighbouring galaxies (e.g., Yun et al 1993Yun et al , 1994Koribalski et al 2003;Koribalski and Dickey 2004;Pearson et al 2016) and in groups/clusters (e.g., Verdes-Montenegro et al 2001;Oosterloo and van Gorkom 2005;Chung et al 2009;English et al 2010;Lee-Waddell et al 2012;Hess et al 2017;Scott et al 2018;Saponara et al 2018). Beyond the inner galaxy disk in which molecular hydrogen is typically the dominant gas component (Leroy et al 2008;Bigiel and Blitz 2012), H I is also an excellent tracer of star formation in the outer discs of galaxies (e.g., Battaglia et al 2006;Koribalski and López-Sánchez 2009;Koribalski 2017).…”
Section: Introductionmentioning
confidence: 99%